Analysis of Student Errors in Solving Basic Logarithmic Problems Using Kastolan Error Analysis - Yodiatmana Yodiatmana; Kartini Kartini (Universitas Maritim Raja Ali Haji, 2022)
This research aims to describe the types of student errors in solving logarithmic problems. The subjects in this study were class X students of SMAN 15 Pekanbaru City, Riau Province. The research method uses a qualitative descriptive approach. Data collection techniques using written tests and documentation. Data analysis used descriptive qualitative analysis by compiling various kinds of student error data as material for research. In this analysis, the types of student errors are categorized based on Kastolan stages. Based on the results of the study, there are still many students who need help solving logarithmic problems. The most errors were conceptual errors at 74.14%, followed by procedural errors at 15.52%, and types of errors with the least technical errors at 10.34%. Conceptual errors indicate a weak understanding of the properties of logarithms, so they cannot apply them. The second type of procedural error occurs due to unsystematic settlement and exit from a predetermined procedure. The kind of error with the lowest percentage is a technique that shows the accuracy of students' calculations in solving problems. This happens because of a need for more thoroughness with the signs that must be used.